Development of D-α-Tocopherol polyethylene glycol 1000 succinate fabricated nanostructural lipid carrier of sorafenib tosylate for metastatic colorectal targeting application: Stability, physical characterization, cytotoxicity, and apoptotic studies against SW48 cells PTEN - Bhattacharya, Sankha; Sharma, Satyam; Prajapati, Bhupendra G. (Frontiers in Oncology, 2022)
The study aimed to create D-α-Tocopherol polyethylene glycol 1000 succinate (TPGS) nanostructured lipid carriers (NLC) of sorafenib tosylate (ST) as lymphatic delivery systems (LDDS) to fight Metastatic colorectal cancer. Initially, ST-SLN, ST-NLC, and ST-LNE were formulated considering oleic acid (OA), glycerol monolinoleate (GMO), glycerol monolinoleate (GML) as solid lipid and further characterised, and tested for stability. The most stable ST-NLC was fabricated with TPGS to produce ST-TPGS-NLC and evaluated by performing in-vitro drug profiling, in-vitro cytotoxicity, and apoptotic studies against human female colorectal adenocarcinoma cell lines (SW48 Cells PTEN). Stability studies on three lipidic nanoparticles (ST-SLN, ST-NLC, ST-LEN) showed particle size, polydispersity index, and zeta potential ranging from 165 nm to 298 nm, 0.125 to 0.288, and -31 mV to -16 mV. At 1600 minutes, more than 80% of ST-NLC1 was released, confirming the sustained release pattern of the formulation. ST-NLC and ST-TPGS-NLC have entrapment efficiencies above 50%. Pure ST's IC50 at 72 hr was 3.45 µg/mL, while 1.56 µg/mL was for ST-TPGS-NLC. The ST-TPGS-NLC reduced the number of livings SW48 Cells PTEN from 91% to 5%, compared to 75% to 8% of pure ST. The ST-TPGS-NLC is a promising LDDS for delivering ST for metastatic colorectal cancer.